Recovery of industrial wastes as fillers in the epoxy thermosets for building application - Hodul, Jakub; Mészárosová, Lenka; Drochytka, Rostislav (MDPI, 2021)
Epoxy resins are currently used in many areas of construction, such as resistant coatings, anchors, fibre-reinforced polymer (FRP) composites, grouts, etc. This paper deals mainly with epoxy composites that can be applied during the rehabilitation of concrete constructions. The influence of a filler type on epoxy thermoset composites was monitored, whilst three different types of epoxy resin were used in order to achieve a better representation and confirmation of the results. During the testing of fillers, these were mainly secondary raw materials, including pre-treated hazardous waste (neutralisation sludge), representing various shapes and sizes of particle, while their amount in the epoxy matrix was chosen with regard to optimal viscosity and workability. Physical and mechanical parameters, like compressive and flexural strengths, cohesion with the concrete and thermal expansion of the epoxy composites containing various fillers were determined. The microstructure of epoxy composites with a different filler type and chemical resistance against chemical aggressive media were all monitored. The microstructure of epoxy composites was monitored using scanning electron microscopy (SEM) supported by energy-dispersive X-ray spectroscopy (EDX). Computed tomography (CT) was also used for the evaluation of the cohesion of the epoxy composites with concrete and dispersion of the filler in the epoxy matrix.

Epoxy resins are currently used in many areas of construction, such as resistant coatings, anchors, fibre-reinforced polymer (FRP) composites, grouts, etc. This paper deals mainly with epoxy composites that can be applied during the rehabilitation of concrete constructions. The influence of a filler type on epoxy thermoset composites was monitored, whilst three different types of epoxy resin were used in order to achieve a better representation and confirmation of the results. During the testing of fillers, these were mainly secondary raw materials, including pre-treated hazardous waste (neutralisation sludge), representing various shapes and sizes of particle, while their amount in the epoxy matrix was chosen with regard to optimal viscosity and workability. Physical and mechanical parameters, like compressive and flexural strengths, cohesion with the concrete and thermal expansion of the epoxy composites containing various fillers were determined. The microstructure of epoxy composites with a different filler type and chemical resistance against chemical aggressive media were all monitored. The microstructure of epoxy composites was monitored using scanning electron microscopy (SEM) supported by energy-dispersive X-ray spectroscopy (EDX). Computed tomography (CT) was also used for the evaluation of the cohesion of the epoxy composites with concrete and dispersion of the filler in the epoxy matrix.
Recovery of industrial wastes as fillers in the epoxy thermosets for building application
Keywords: epoxy resin; filler; composite; adhesion; chemical resistance; microstructure; strength; epoxy resin; filler; composite; adhesion; chemical resistance; microstructure; strength